Prevalence of Cryptosporidiosis in Calves and Efficiency of ELISA in Detection of The Infection Compared with Some Traditional Methods: Muna M. Khalil Mohammad TH. S. Al- Zubaidi* Fawzia S. Kadhim - Khalil, Muna M. (The Iraqi Journal of Veterinary Medicine, 2011)
Cryptosporidiosis is one of the main causes of economical losses in calf breeding farms due to the diarrhea which results from the infection with this parasite. Diagnostic methods for detection of this infection vary in their efficiency. This study aimed to investigate the prevalence of cryptosporidial infection in Al-Nasr station and compare the efficiency of ELISA in detection of cryptosporidial oocysts with some traditional laboratory methods. A total of 422 faecal samples were collected from three groups of 1-30 day-old calves of both sexes during the period from November 2009 to April 2010. The first group was suffering from watery diarrhea , the second group had pasty faeces, while the third group was normal calves. The first 92 samples were examined with three laboratory methods : Modified Zeihl -Neelsen stain, Floatation with saturated sugar solution, and ELISA, whereas the remained samples were examined with the two first methods only . The overall infection rate with Cryptosporidium in young calves was 34.83 %. The oocysts stained with Modified Zeihl-Neelsen appeared spherical or oval in shape and had red colour. The average oocysts measurement was 4.45.2μm. Calves 6-10 day-old had the highest rate of infection (61.25%), while the lowest infection rate was among calves 26-30 days – old 13.33% (P<0.05). Male and female had very close rate of infection (34 % and 35.09% respectively). Regarding faeces consistency, 48.29 % of calves with diarrhea was infected compared with 36.36 % of calves with pasty faeces and 19.58 % of normal calves. The highest rate of infection was recorded in April (41.25%) while the lowest rate was in November 27.14% (P0.01). The study revealed no significant differences in the efficiency of ELISA in detecting cryptosporidial oocysts in faecal samples when compared with traditional laboratory methods. Among 92 examined samples ELISA gave 35 positive results (38.04%) compared with 34 positive samples (36.95%) for each of MZN and floatation with saturated sugar solution.